2013
DOI: 10.1063/1.4817090
|View full text |Cite
|
Sign up to set email alerts
|

Gene delivery in conjunction with gold nanoparticle and tumor treating electric field

Abstract: The advances in electrotherapy to treat the diseased biological cell instigate its extension in gene therapy through the delivery of gene into the nucleus. The objective of this study is to investigate the application of moderate intensity alternating electric field, also known as tumor treating electric field on a carrier system consisting of a charged gene complex conjugated to the surface of a gold nanoparticle. The gene delivery mechanism relies on the magnitude and direction of the induced electric field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Also, the plot in Figure 9(b) shows the relative percentage of light scattering of the average particle size and the distinct peak was found at 91.28 nm, which indicates the presence of nanoscale aggregates within the samples. This result was compared to that found in the literature and was found to be similar [66,67].…”
Section: Dynamic Light Scattering (Dls) and Zeta Potentialsupporting
confidence: 59%
“…Also, the plot in Figure 9(b) shows the relative percentage of light scattering of the average particle size and the distinct peak was found at 91.28 nm, which indicates the presence of nanoscale aggregates within the samples. This result was compared to that found in the literature and was found to be similar [66,67].…”
Section: Dynamic Light Scattering (Dls) and Zeta Potentialsupporting
confidence: 59%
“…The NPs are capable of attaching to the bacterial membrane by electrostatic interaction and disrupt its integrity [24]. They can change membrane potential and decrease ATP levels within the cell and inhibit the binding of tRNA with ribosomal subunit, affecting translation [25].…”
Section: Mechanism Of Antibacterial Activity Of Gold Nanoparticlesmentioning
confidence: 99%
“…HER2 over-expression leads to cancerous cell proliferation and is seen in cancers such as breast cancer, ovarian cancer, stomach cancer, and even lung cancer 27 , and both SKOV3 and MCF7 cells over-express HER2 markers on their surface membrane. It has also been shown that in the presence of an electric field, AuNPs could change the distribution of the field within the cell's cytoplasm resulting in an inward net electric force which potentially could change the function of the cell 28 . Thus, further experiments specifically targeting the two types of cancer cells using HER2 antibody functionalized gold nanoparticles (HER2-AuNPs) were performed to determine if enhanced electric field strength can be induced via the application of nanoparticles, consequently leading to the killing of the cancerous cells without affecting non cancerous HUVECs and MCF10a providing a platform for the development of a non-invasive cancer treatment without any harmful side effects.…”
Section: Introductionmentioning
confidence: 99%